ANALISA TEKNIS PENGUJIAN KEKEDAPAN PENGELASAN PADA TANGKI TONGKANG DENGAN MEMBANDINGKAN METODE CHALK TEST, AIR PRESSURE TEST DAN VACUUM TEST - Firda Herlina; M. Suprapto; Siswanto Siswanto (Universitas Lambung Mangkurat, 2018)
PT. Dock & amp; perkapalan kodja nautical ( persero ) shipyard banjarmasin is a company that move in ship industry, development for shipbuilding industry large enough aims to meet the needs of countries will ships as a country maritime .In doing their activities, company got a job as the construction of ships new, work a serviceman a ship etc. The field of that is associated with welding, welding identical also with a flaw and fraud especially on the part affected a serviceman . Testing impermeability a tank were done in order to the examination of the possibility of mismanagement of a connection is welding and why ensure the quality of welds, an adequate number of qualified to leakage in the connection las can be seen from that there was an indication who occuring when testing done in the same manner .There are several a method of testing, and among the companies were a method of lime oil , water test and a vacuum test drives in .Chalk test drives in / lime oil is a method of welding stability testing traditional tank , water pressure test drives in is a method of welding stability testing a tank by the principle of the compressed air and a vacuum test drives in also made use of of the nature of soapy water , only on the implementation of the activity a method of testing is provided by way of an instrument a vacuum box shaped with one of the sides open and one of the sides made from the materials of glass . In the process of testing kekedapan welding a method of the most accurate in a reading of a point to leakage in connection las that is a method of water pressure test/the compressed air with flattened flattened a reading of a point leakage is more than 1 in any its testing. A method of tests need time in at least the process that is a method of vacuum test and water pressure test.Testing first method vacuum test 1.15 hours and water pressure test by 0.47 hours. Testing second method vacuum test 1.30 hours and water pressure test 1.20 hours. Testing third method vacuum test 0.40 hours and water pressure test 0.50 hours. Testing fourth method vacuum test 1.15 hours and water pressure test 1.20 hours. Testing fifth method vacuum test .30 hours and water pressure test 0.37 hours. Testing sixth method vacuum test 1.40 hours and water pressure test 1.30 hours.